Cyanobacterial Allelochemicals But Not Cyanobacterial Cells Markedly Reduce Microbial Community Diversity - Dias, Filipa; Antunes, Jorge T.; Ribeiro, Tiago; Azevedo, Joana; Vasconcelos, Vitor; Leão, Pedro N. (Frontiers in Microbiology, 2017)
The freshwater cyanobacterium Phormidium sp. LEGE 05292 produces allelochemicals, including the cyclic depsipeptides portoamides, that influence the growth of heterotrophic bacteria, cyanobacteria and eukaryotic algae. Using 16S rRNA gene amplicon metagenomics, we show here that, under laboratory conditions, the mixture of metabolites exuded by Phormidium sp. LEGE 05292 markedly reduces the diversity of a natural planktonic microbial community. Exposure of the same community to the portoamides alone resulted in a similar outcome. In both cases, after 16 days, alpha-diversity estimates for the allelochemical-exposed communities were less than half of those for the control communities. Photosynthetic organisms, but also different heterotrophic-bacteria taxa were found to be negatively impacted by the allelochemicals. Intriguingly, when Phormidium sp. LEGE 05292 was co-cultured with the microbial community, the latter remained stable and closer to a non-exposed community than to the allelochemical-exposed communities. Overall, our observations suggest that although under optimal growth conditions Phormidium sp. LEGE 05292 is able to synthesize potent allelochemicals that severely impact microbial communities, its allelopathic effect is not pronounced when in contact with a complex microbial community. These observations suggest that under more ecologically-relevant conditions, the allelopathic behavior of this cyanobacterium may be downregulated or even mitigated by interactions with surrounding microbiota.